Combination of anti-C1qA08 and anti-mCRP a.a.35-47 antibodies is associated with renal prognosis of patients with lupus nephritis - Liu, Xiao-Ling; Tan, Ying; Yu, Feng; Ji, Shang-Rong; Zhao, Ming-Hui (Frontiers in Immunology, 2023)
Objective. The aim of this study is to explore the prevalence and clinicopathological associations between anti-C1qA08 antibodies and anti-monomeric CRP (mCRP) a.a.35-47 antibodies and to explore the interaction between C1q and mCRP. Methods. Ninety patients with biopsy-proven lupus nephritis were included from a Chinese cohort. Plasma samples collected on the day of renal biopsy were tested for anti-C1qA08 antibodies and anti-mCRP a.a.35-47 antibodies. The associations between these two autoantibodies and clinicopathologic features and long-term prognosis were analyzed. The interaction between C1q and mCRP was further investigated by ELISA, and the key linear epitopes of the combination of cholesterol binding sequence (CBS; a.a.35-47) and C1qA08 were tested by competitive inhibition assays. The surface plasmon resonance (SPR) was used to further verify the results. Results. The prevalence of anti-C1qA08 antibodies and anti-mCRP a.a.35-47 antibodies were 50/90 (61.1%) and 45/90 (50.0%), respectively. Levels of anti-C1qA08 antibodies and anti-mCRP a.a.35-47 antibodies were negatively correlated with serum C3 concentrations ((0.5(0.22-1.19) g/L vs. 0.39(0.15-1.38) g/L, P=0.002) and (0.48(0.44-0.88) g/L vs. 0.41(0.15-1.38) g/L, P=0.028), respectively. Levels of anti-C1qA08 antibodies were correlated with the score of fibrous crescents and tubular atrophy (r=-0.256, P=0.014 and r=-0.25, P=0.016, respectively). The patients with double positive antibodies showed worse renal prognosis than that of the double negative group (HR 0.899 (95% CI: 0.739-1.059), P=0.0336). The binding of mCRP to C1q was confirmed by ELISA. The key linear epitopes of the combination were a.a.35-47 and C1qA08, which were confirmed by competitive inhibition experiments and SPR. Conclusion. The combination of anti-C1qA08 and anti-mCRP a.a.35-47 autoantibodies could predict a poor renal outcome. The key linear epitopes of the combination of C1q and mCRP were C1qA08 and a.a.35-47. A08 was an important epitope for the classical pathway complement activation and a.a.35-47 could inhibit this process.